Exploring the Competency Elements of Building Construction Site Managers for G3 Class Contractors - Wan Mohamed Tirmizi, Wan Nor Fazlina; Hamid, Hashima (Research and Innovation in Technical and Vocational Education and Training, 2024)
This study was conducted to explore the elements of competence of building site managers among the latest G3 class contractors in Malaysia. Contractors can choose competent workers in the construction sector to make sure the project can be delivered very well. This study uses a qualitative method by interviewing experts who are experienced and active in the construction sector to obtain the elements of competence that are needed nowadays in terms of technical and non-technical skills. The results of this study show that there are four elements of construction site manager competence for class G3 contractors, which are divided into two parts, namely technical and non-technical skills. The elements of technical skills are knowledge and skills. Meanwhile, the elements of non-technical skills are communication, critical thinking discipline, and trust in technical skills, and three elements of non-technical skills. Finally, it can be concluded that hiring someone to be a site supervisor needs to emphasize criteria and skills that are suitable for the scope of work that will be the responsibility of the construction site supervisor.